ANOMALOUS ORIGIN OF THE EPICARDIAL LEFT CORONARY ARTERY FROM THE RIGHT CORONARY SINUS REVEALED IN A PATIENT PRESENTING WITH ACUTE MYOCARDIAL INFARCTION - Khan, Habib Rehman; Hashim, Hashim; Bhandari, Manoj (Journal of Ayub Medical College Abbottabad, 2016)
An 84-year-old lady presented with history of syncope and a transient loss of consciousness proceeded by severe chest pain to accident and emergency. Electrocardiogram (ECG) revealed anterolateral ST elevation. She had an emergency coronary angiogram revealing an anomalous left coronary artery with severe tortuosity and occlusion at mid segment. During the course of the angiogram she became asymptomatic and TIMI flow spontaneously restored. These findings were discussed with the patient and she opted for medical management understanding that it would be difficult to negotiate the tortuosity. On follow up she remained well with optimal anti-anginal treatment Keywords: Myocardial infacrtion, anomalous, angiography, coronary artery